POLITICAL ECONOMY OF LABOUR AND DEVELOPMENT IN KERALA: Some Reflections on the Dilemmas of a Socially Transforming Labour Force in a Slow Growing Economy - Kannan, FP (Centre for Development Studies-WP284, 1998)
Kerala is well-known for its achievements in the sphere of social development that includes a rapid and high level mobilisation and organisation of workers regardless of location and sectoral occupation. However such a process of social development without a commensurate transformation of the productive sectors has presented Kerala with some major dilemmas. This paper therefore takes a critical look at the political economy of labour and development by examining the roles of labour unions, state, and capital. The three dilemmmas relate to (i) technological choice in the face of high and rising labour costs in labour-intensive activities for maximising long-term growth and employment, (ii) mismatch between labour-supply and labour demand as a result of changing job expectations of the younger generation in a technologically stagnant economy, and (iii) lack of new investment despite growing loanable funds and declining resistance to technological change. The failure of labour unions to agree to productivity improvements through technological changes and increasingly resorting to 'closed shop' strategies has been particularly emphasised